Pedagogical Leaders’ Approaches to Promoting Inclusion of Children with Autism in Norwegian Kindergartens - Trine Andrea Boquist; Magnar Ødegård; Henri Valtteri Pesonen (Education Sciences)
It is well recognized that Norwegian kindergartens have an important role in ensuring inclusion among all children, but the actual implementation of inclusive practices can vary greatly in early childhood education. Particularly how the inclusion of children with Autism Spectrum Disorder (ASD) is supported in kindergartens has raised concerns, and research focusing on the current circumstances in Norway is scarce. To fill in this gap in research, our study examined pedagogical leaders’ approaches to promoting inclusion of children with autism in kindergartens. The method of empathy-based stories (MEBS) was used to collect stories from 32 participants working in kindergartens. Qualitative analysis of participant produced stories revealed that inclusion of children with autism consisted of two themes: (1) professional framework for inclusion and (2) empathetic approaches to inclusion. The findings provide suggestions for further research and development work related to inclusion of children with ASD in early childhood education.